2017
DOI: 10.1111/1744-7917.12496
|View full text |Cite
|
Sign up to set email alerts
|

Avoidance of parasitized host by female wasps of Aphidius gifuensis (Hymenoptera: Braconidae): The role of natal rearing effects and host availability?

Abstract: Natal rearing experience of animals may affect their behaviors, such as habitat selection and oviposition decision. As part of the overall fitness of insect parasitoids, successful host discrimination (distinguishing parasitized hosts from unparasitized hosts) is of paramount importance. In this study we examined whether and how parasitoids' natal rearing experience would affect their host discrimination ability according to host availability. We established separate colonies of Aphidius gifuensis Ashmead by c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…In China, this wasp has been widely bred and used as a biocontrol agent for more than four decades to control the green peach aphid, Myzus persicae , a severe pest on vegetables and tobaccos (Li et al, 2018; Yang et al, 2011). The life history, physiological characteristics, parasitic ability and breeding technology of A. gifuensis have been extensively studied to improve its captive breeding behaviour and aphid control efficiency (Khan et al, 2016; Li et al, 2013; Pan et al, 2018; Yang et al, 2009). For instance, using comparative transcriptome and proteome analysis, Zhang et al (2018) identified genes associated with diapause behaviour.…”
Section: Introductionmentioning
confidence: 99%
“…In China, this wasp has been widely bred and used as a biocontrol agent for more than four decades to control the green peach aphid, Myzus persicae , a severe pest on vegetables and tobaccos (Li et al, 2018; Yang et al, 2011). The life history, physiological characteristics, parasitic ability and breeding technology of A. gifuensis have been extensively studied to improve its captive breeding behaviour and aphid control efficiency (Khan et al, 2016; Li et al, 2013; Pan et al, 2018; Yang et al, 2009). For instance, using comparative transcriptome and proteome analysis, Zhang et al (2018) identified genes associated with diapause behaviour.…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, A. gifuensis showed higher parasitoid preference and suitability on its maternal host aphids than other aphid species [30]. Natal rearing experience affects the host discrimination and oviposition decision of A. gifuensis [36]. Due to the importance of neuropeptides and their receptors in the modulation of insect behavior, all of these results indicated that neuropeptides and their receptors in A. gifuensis may play a critical role in the odor perception and successful parasitism.…”
Section: Discussionmentioning
confidence: 75%
“…A. gifuensis female is able to discriminate the plant volatiles that released from healthy, mechanically damaged or aphid infested plant [35]. Furthermore, when provided with various aphid species, the A. gifuensis female can adjust its parasitic strategy by laying fewer eggs in maternal aphid species and more eggs in other aphid species [30,36]. Interestingly, both virgin and mated A. gifuensis females show high preference of aphid alarm pheromone, E-(β)-farnesene [37].…”
Section: Introductionmentioning
confidence: 99%
“…Mass rearing of BCAs on alternative foods may reduce their performance during the rearing period or after release upon encountering the target prey in the field [80]. Researchers have demonstrated that the natal rearing experience of parasitoids may affect their behavioral and physiological characteristics [80][81][82][83]. Ghaemmaghami et al [84] found that laboratory mass-reared colonies of T. brassicae (Hymenoptera: Trichogrammatidae) declined in quality after 15 generations.…”
Section: Discussionmentioning
confidence: 99%